2006
DOI: 10.1258/004947506778604968
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of paediatric renal disease in inpatients in Calabar, Nigeria

Abstract: A 10-year retrospective review of inpatients in Calabar showed that of 5641 children admitted,182 (3.2%) had renal disease. The major lesions were acute glomerulonephritis (36.9%) and nephrotic syndrome (30.7%), while less common ones included urinary tract infection (8.9%), obstructive uropathy, acute renal failure (6.7%, each) and nephroblastoma (6.2%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 2 publications
6
13
4
Order By: Relevance
“…Studies from different parts of Nigeria and the world have reported variable patterns of renal diseases in children. Though our prevalence of 3.2% was low and may not be significant, it was similar to the 3.2% obtained in Calabar, [5] 3.9% in Lagos, [6] 3.0% in Libya, [7] and 3.3% in Pakistan. [8] However, it was lower than the 4.0% reported by Okoro et al [9] in Enugu and 6.3% by Bhatta et al [10] in Nepal.…”
Section: Discussionsupporting
confidence: 82%
“…Studies from different parts of Nigeria and the world have reported variable patterns of renal diseases in children. Though our prevalence of 3.2% was low and may not be significant, it was similar to the 3.2% obtained in Calabar, [5] 3.9% in Lagos, [6] 3.0% in Libya, [7] and 3.3% in Pakistan. [8] However, it was lower than the 4.0% reported by Okoro et al [9] in Enugu and 6.3% by Bhatta et al [10] in Nepal.…”
Section: Discussionsupporting
confidence: 82%
“…For instance, reports from Enugu (Okafor et al, 1995), Port Harcourt (Eke and Nte, 1994), and Zaria (Akhionbare and Abdulrahman, 1984) have indicated increasing yearly incidence of this condition as against earlier reports from Ibadan and other parts of the world (Meadow 1975;Etuk et al 2006;Antia, 1995). In most parts of the developing world, including Nigeria, paediatric cases of AGN is largely associated with streptococcal infection of the throat and skin, a situation closely linked to low socio-economic status and poor environmental hygiene (Bello, 1991).…”
Section: Introductionmentioning
confidence: 90%
“…The epidemiology and clinical features of AGN tend to vary with place and time within Africa (Travis1978; Etuk et al, 2006). For instance, reports from Enugu (Okafor et al, 1995), Port Harcourt (Eke and Nte, 1994), and Zaria (Akhionbare and Abdulrahman, 1984) have indicated increasing yearly incidence of this condition as against earlier reports from Ibadan and other parts of the world (Meadow 1975;Etuk et al 2006;Antia, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, urinary tract infection, acute glomerulonephritis and nephrotic syndrome can be considered as risk factors for the development of chronic kidney disease if not detected early and managed promptly (6,7) .…”
Section: Introductionmentioning
confidence: 99%